Teacher's Strategies in Using Target Language in EFL Classroom - Eka Nurhidayat; Eva Fitriani Syarifah; madani, el (Papanda Journal of English Education, 2023)
English is mostly taught in a classroom setting in a foreign language context. However, English is not always spoken or exposed to; even in the classroom, hardly ever use English. This situation suggests that full English classes are utilized quite frequently and first language is occasionally required. This research aims to reveal the teacher’s strategies in using target language (TL) in EFL classroom and to reveal the teacher’s perceptions toward the use of target language in EFL classroom. This research used a qualitative method with a case study design. The participants of this research were a teacher that teaching English in one of the senior high schools in Majalengka. The result shows the teacher tries to maximize the use of English as the target language in classroom by using several strategies, they are: using the same or similar instruction and gestures, ‘guess’ the meaning based on the context, speak more slowly and deliberate, strategy pausing, modifying the pronunciation, vocabulary use is more basic, simplifying grammar and letting student speaks. The teacher realized that the English classroom and the English teacher were the only source of learning English. The teacher tries to maximize the use of English as the target language in classroom. This is to fulfil the opportunity to learn English for students. And teachers also believe that getting used to English in classroom can improve students' abilities in English. This research was not conducted deeply and the writer realized there are many weaknesses in it. This research also allows the other researcher to research new things behind English as a medium of instruction and the researcher suggests to other researchers to involve more participants and longer time.